Membangun Dialog Antaragama secara Autentik Berdasarkan Pemikiran Masao Abe - Reinaldo Patricio Tedja; Albertus Ananda Orlando; Andreas Rahul Pratama; Albert Arysatya Ray Raja (Fakultas Teologi, Universitas Sanata Dharma, 2026)
Religious intolerance and discrimination remain serious issues in Indonesia, threatening social harmony within its pluralistic society. This reality highlights the urgent need to foster authentic interreligious dialogue as a bridge toward mutual understanding. This study examines the thought of Masao Abe, a Japanese Buddhist philosopher from the Kyoto School, who offers a transformative perspective on interreligious dialogue. Two main questions are formulated: how does Masao Abe understand the nature of interreligious dialogue, and how can his ideas be applied within the context of religious pluralism in Indonesia? Using a qualitative method with a literature study approach, this research analyzes Abe’s key works as well as secondary literature related to interreligious dialogue and pluralism. The findings show that, according to Abe, interreligious dialogue is not merely a formal conversation or religious diplomacy, but a radical inner openness to learn from other traditions by letting go of the claim to absolute truth. Genuine dialogue requires the willingness to transcend doctrinal boundaries in the search for a shared truth that recognizes the universal dimensions of humanity and divinity. In the Indonesian context, Abe’s thought can be implemented through multicultural education that emphasizes deep understanding of other religious traditions, the establishment of sustainable interfaith forums, and the cultivation of epistemological humility in embracing diversity. This study concludes that Masao Abe’s model of interreligious dialogue can serve as a strong foundation for fostering harmony, reducing intolerance, and strengthening social cohesion amid Indonesia’s plural society.AbstrakIntoleransi dan diskriminasi berbasis agama masih menjadi persoalan serius di Indonesia, yang mengancam harmoni sosial dalam masyarakat yang majemuk. Realitas ini menunjukkan urgensi membangun dialog antaragama yang autentik untuk menemukan jembatan hidup saling memahami. Penelitian ini mengkaji pemikiran Masao Abe, filsuf Buddhis Jepang dari Sekolah Kyoto, yang menawarkan perspektif transformatif tentang dialog antaragama. Dua pertanyaan utama yang dirumuskan adalah: bagaimana Masao Abe memahami hakikat dialog antaragama, dan bagaimana pemikirannya dapat diaplikasikan dalam konteks pluralisme agama di Indonesia. Menggunakan metode kualitatif dengan pendekatan studi kepustakaan, penelitian ini menelaah karya-karya utama Masao Abe serta literatur sekunder terkait dialog antaragama dan pluralisme. Hasil penelitian menunjukkan bahwa menurut Abe, dialog antaragama bukan sekadar percakapan formal atau diplomasi keagamaan, melainkan keterbukaan batin yang radikal untuk belajar dari tradisi lain dengan melepaskan klaim absolutisme kebenaran. Dialog sejati menuntut kesediaan untuk melampaui batas-batas doktrin demi pencarian kebenaran bersama yang mengakui dimensi kemanusiaan dan keilahian secara universal. Dalam konteks Indonesia, pemikiran Abe dapat diimplementasikan melalui pendidikan multikultural yang menekankan pemahaman mendalam terhadap tradisi keagamaan lain, pembentukan forum lintas iman yang berkelanjutan, serta pengembangan sikap kerendahan hati epistemologis dalam menerima keragaman. Penelitian ini menegaskan bahwa dialog antaragama model Masao Abe dapat menjadi landasan kokoh untuk membangun kerukunan, mengikis intoleransi, dan memperkuat kohesi sosial di tengah pluralitas masyarakat Indonesia.